Sternoclavicular joint tuberculosis masquerading as neck abscess - Mathew, Cynthia Susan; Mathews, Suma Susan; Albert, Rita Ruby A (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Tuberculosis of the sternoclavicular joint is uncommon and management of tuberculosis can be challenging in the background of systemic illness like chronic liver disease as some of the first line drugs are hepatotoxic. Here we reported a case of 47 year old man who presented with a neck swelling noticed following a blunt trauma and record the clinical presentation, laboratory investigations, imaging findings. With the imaging studies and fine needle aspiration of the swelling detecting acid fast bacilli using TB PCR test, the diagnosis was arrived at. This case report illustrates the unusual presentation of extra pulmonary TB and selection of the anti-TB drugs in chronic liver disease.